Digital agriculture’s equalization effect in the Yangtze River economic belt: An empirical study using difference-in-difference analysis - Bi, Xiongfei (Edelweiss Applied Science and Technology, 2025)
To achieve common prosperity in China, digital agricultural transformation is increasingly important in narrowing the income gap and promoting rural revitalization. Based on a quasi-natural experiment involving digital agriculture pilot projects in the Yangtze River Economic Belt, this paper systematically evaluates the impact of digital agriculture policies on common prosperity using data from the China Family Panel Studies (CFPS) from 2012 to 2022, employing a difference-in-difference (DID) approach. The study finds that digital agriculture policies significantly reduce residents’ subjective perceptions of income inequality, with a particularly significant effect in the central and western regions and among households engaged in agriculture. Mechanism analysis suggests that the policies form a positive chain of pathways that mitigate income inequality by improving the modernization of agricultural production tools, optimizing resource allocation efficiency, and increasing farmers’ income. Heterogeneity analysis reveals significant heterogeneity in policy effects across regions and population groups. The marginal utility of the policies is higher in the central and western regions due to their weak agricultural foundations, while the incremental effect is relatively limited in the eastern region due to its advanced agricultural modernization. This study provides empirical evidence for digital agriculture’s contribution to common prosperity and offers a reference for policymakers to optimize digital agriculture promotion strategies and promote balanced regional development.